Effect of optimized thrombus aspiration on myocardial perfusion and prognosis in acute ST-segment elevation myocardial infarction patients with primary percutaneous coronary intervention - Boning Xu; Chunxin Zhang; Wei Wei; Yun Zhan; Mingguo Yang; Yanjun Wang; Jiajian Zhao; Guiyang Lin; Wen-wen zhang; Xing Huo; Bin Shi; Ling Fan (Frontiers in Cardiovascular Medicine, 2023)
ObjectiveTo investigate the impact of optimized thrombus aspiration on myocardial perfusion, prognosis, and safety in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention(primary PCI).MethodsA total of 129 patients with STEMI were randomly allocated into control group (Subgroup A and B) and experimental group(Subgroup C and D). Control group received percutaneous transluminal coronary angioplasty (PTCA),thrombus aspiration and primary PCI. Experimental group received optimized thrombus aspiration and primary PCI. The number of thrombus aspiration was less than 4 times in Subgroup A and C. The number of thrombus aspiration was performed more than 4 times in Subgroups B and D. The classification of thrombi extracted, the TIMI flow grade, the incidence of no-reflow and slow flow, cTFC, TPI and CK-MB at 12 h and 24 h after stenting, ST segment resolution of ECG after stenting, NT-proBNP, LVEFat 24 h, 30 days and 180 days after stenting were compared between groups. The incidence of intraoperative and postoperative bleeding complications, stroke events and major cardiovascular events (MACE) were recorded and compared between groups.ResultsThe classification of thrombi extracted in the experimental group was higher than that in the control group. The TIMI flow grade of the experimental group was better than the control group after thrombus aspiration. After stenting, the advantage still existed, but the difference was not statistically significant. On cTFC, the experimental group was lower than the control group, but the difference was not statistically significant; After stenting the experimental group was significantly lower than the control group. The CK-MB at 12 h and 24 h of the experimental group was lower than the control group. After thrombus aspiration the incidence of no-reflow in the experimental group was significantly lower than that in the control group; after stenting the incidence of no-reflow in the experimental group was still lower than the control group, but no statistically difference. After thrombus aspiration and stenting the incidence of slow flow in the experimental group were lower than that in the control group. After stenting, NT-proBNP at 24 h was lower in the experimental group than that in the control group, However, there was no statistical difference; after stenting, The NT-proBNP in the experimental group was lower than that in the control group at 30 days and 180 days. After stenting, LVEF of the experimental group was significantly higher than the control group at 24 h and 30 days; superiority remained after 180 days but no statistical difference. There was no statistical difference between two groups for intraoperative and postoperative bleeding complications, stroke events, and MACE events. In Subgroup analysis,there was no significant difference in the classification of thrombi extracted, TIMI flow grade, cTFC, CK-MB,NT-proBNP and LVEF between group C and D, but group A was better than group B. Analysis of variance showed that the optimal number of suction was 4–5 times.ConclusionsOptimized thrombus aspiration can significantly improve myocardial perfusion and short-term and medium-term prognosis of STEMI patients after PCI, and reduce the incidence of slow flow and no-reflow. The optimal suction times were 4–5 times. Traditional aspiration method with more aspiration times is harmful to cardiac prognosis. Thrombus aspiration does not increase the incidence of stroke events and is safe.Clinical Trial Registration: identifier, ChiCTR2300073410.